2012
DOI: 10.1155/2012/475731
|View full text |Cite
|
Sign up to set email alerts
|

Before It Gets Started: Regulating Translation at the 5′ UTR

Abstract: Translation regulation plays important roles in both normal physiological conditions and diseases states. This regulation requires cis-regulatory elements located mostly in 5′ and 3′ UTRs and trans-regulatory factors (e.g., RNA binding proteins (RBPs)) which recognize specific RNA features and interact with the translation machinery to modulate its activity. In this paper, we discuss important aspects of 5′ UTR-mediated regulation by providing an overview of the characteristics and the function of the main ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
192
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(207 citation statements)
references
References 65 publications
8
192
0
7
Order By: Relevance
“…S1). The region of 30-50 nt downstream from the 5 ′ cap is known to be bound by a 40S ribosomal subunit during formation of the 43S pre-initiation complex (Araujo et al 2012), and this process initiates capdependent gene translation. Recently published studies suggest that miRNAs repress gene translation by impairing the function of the pre-initiation complex (Meijer et al 2013;Ricci et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). The region of 30-50 nt downstream from the 5 ′ cap is known to be bound by a 40S ribosomal subunit during formation of the 43S pre-initiation complex (Araujo et al 2012), and this process initiates capdependent gene translation. Recently published studies suggest that miRNAs repress gene translation by impairing the function of the pre-initiation complex (Meijer et al 2013;Ricci et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have shown that the 5 ′ UTR performs an important regulatory function in posttranscriptional processes (Davuluri et al 2000;Pickering and Willis 2005;Ringnér and Krogh 2005;Araujo et al 2012). First, the 5 ′ UTR contains several regulatory elements, such as binding sites for RNA binding proteins (RBPs), upstream open reading frames (uORFs), and upstream start codons (uAUGs), which have a great impact on the regulation of translation (Araujo et al 2012). Second, the mRNA secondary structure of the 5 ′ UTR has been recognized as a major feature that regulates gene translation (Pickering and Willis 2005).…”
Section: Thementioning
confidence: 99%
“…[25][26][27] The 5'UTRs can differ in length, nucleotide content, secondary structures, and the presence of different functional elements. 28 The main regulatory elements in 5'UTRs are secondary structures, including internal ribosome entry sites (IRESes), upstream open reading frames (uORFs) and upstream AUG codons (uAUGs), as well as binding sites for RNA-binding proteins. 29 These cisregulatory elements can affect the stability or translational efficiency of mRNAs, resulting in a rapid alteration of protein level in response to internal and external stimuli, without the need for new mRNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, uORF are important regulators of translation, particularly in response to nutritional and metabolic stress (80). The OPN-5 uORF may therefore serve to regulate the translational efficiency of the OPN-5 protein under certain metabolic conditions.…”
Section: Osteopontin Splice Variantsevidence For Association With Spementioning
confidence: 99%